THE SCIENTIFIC LEGACY OF MUHAMMAD SHARIF JURJANI AND ITS PHILOSOPHICAL SIGNIFICANCE FOR THE DEVELOPMENT OF HUMAN THOUGHT (Scientific journal of the Fergana State University, 2026)
This article is devoted to the study of Muhammad Sharif Jurjani’s scientific legacy and its philosophical significance for the development of human thought. The paper analyzes the scholar’s scientific activity in Samarkand, his philosophical views, and their impact on the formation of human thinking. In addition, it examines aspects related to Jurjani’s legacy in shaping modern human spirituality, ethical decision-making, and the development of social values.